Synthesis of Chitosan/Activated Carbon Composite Beads as an Adsorbent of Pb(II) and Cu(II) ions in Aqueous Solution: A Review (Universitas Negeri Semarang, 2022)
Water is the most important substance for the life of living things. The development of various industries causes water pollution by metal ions. Adsorption is a way to remove metal ions in water. The adsorbents commonly used for adsorption are chitosan and activated carbon. Chitosan has weaknesses such as being easily soluble in acid, low selectivity, and less strong mechanical strength. One way to improve the properties of chitosan is to modify it with activated carbon. In this study, a literature review was conducted on the manufacture of chitosan/activated carbon composite beads for Pb(II) and Cu(II) ions adsorbents. Reference sources articles obtained from the Google Scholar database were selected using exclusion and inclusion criteria. The results obtained from the literature review show that chitosan/activated carbon can be made by dissolving chitosan in a CH3COOH solution, adding with activated carbon to form a mixture and the mixture is formed into beads by dripping it into a NaOH solution. The adsorption process of chitosan/activated carbon is influenced by pH, contact time, and solution concentration. The reaction mechanism that occurs is thought to be through electrostatic bonds, the formation of complex compounds, and the pores of the adsorbent. Chitosan/activated carbon adsorbent is an adsorbent that can be regenerated and reused for adsorption 5 times.